Moderating effect of profitability on intellectual capital and real earnings management - Sistya Rachmawati (The Accounting Journal of Binaniaga, 2020)
This study aims to determine (1) Effect of intellectual capital, on real earnings management (2) Effect of capital employed efficiency (CEE) on real earnings management (3) Effect of structural capital efficiency (SCE) on real earnings management (4) Effect of human capital efficiency (HCE) on real earnings management (5) Profitability as a moderating variable can strengthen the effect of intellectual capital on real earnings management. Sample collection was carried out using purposive sampling and produced a sample of 80 companies during the 20152017 period which was 240 companies. The analytical tool used is multiple linear regression with the Fixed Effect method. The results of the study show that intellectual capital has a negative effect on real earnings management. Neither can profitability strengthen the effect of intellectual capital on real earnings management. Whereas the control variable which has a significant influence on real earnings management is earnings growth. Keywords: Real Earnings Management, Profitability, Intellectual Capital